Odsetki od kredytowanej prowizji a Rzeczywista Roczna Stopa Oprocentowania kredytu konsumenckiego - Mędrzecka, Joanna (PRAWO i WIĘŹ, 2024)
The aim of the paper is to consider the acceptability in the Polish legal system of crediting a commission by an entrepreneur to a consumer for granting a loan, and in particular the admissibility of charging interest on the amount granted to the consumer in order to credit such a commission. The subject of the article is also the issue of correct calculation of the annual interest rate on consumer credit for cases in which the commission related to granting the loan is credited to the consumer. An important issue is also whether the crediting of the commission, understood as the granting of a loan to the consumer by the entrepreneur to cover the commission and charging interest on the part of the loan repaid in loan installments, may entitle the consumer to submit a statement on the use of the sanction of free credit, and thus to return the loan without interest and other fees. Another practically significant legal problem is the problem of whether a clear indication in the agreement that the lender will charge interest on the credited commission, resulting in the informed consent of the consumer borrower to such content of the legal relationship, is relevant for both parties to be bound by the concluded agreement. These problems have gained great practical significance due to the fact that specialized companies have appeared on the market, which professionally deal with the purchase of claims from consumers resulting from loan agreements for a fraction of their value.